Drought-Responsive Hsp70 Gene Analysis in Populus at Genome-Wide Level - Yer, Esra Nurten; Baloglu, Mehmet Cengiz; Ziplar, Ummugulsum Tanman; Ayan, Sezgin; Unver, Turgay (Springer Science and Business Media LLC, 2015)
The heat shock protein 70 (Hsp70) family members are known as molecular chaperones. They play a crucial role in protecting plant cells and tissues from thermal or abiotic stress through protein folding and in assembly, stabilization, activation, and degradation processes. Although many studies have been performed to identify molecular functions of individual family members, there is a limited study on genome-wide identification and characterizations of Hsps in the Populus model tree genus. We have identified 34 poplar Hsp70 genes, which were phylogenetically clustered into three major groups. Gene structure and motif composition are relatively conserved in each group. Mainly tandem and infrequently segmental duplications have a significant role in poplar Hsp70 gene expansion. The in silico microRNA (miRNA) and target transcript analyses identified that a total of 19 PtHsp70 genes were targeted by 27 plant miRNAs. PtHSP70-14 and PtHSP70-33 are the most targeted by miR390 and miR414 family members, respectively. For determination of drought response to Hsp70 genes, publicly available RNA-seq data were analyzed. Poplar Hsp70s are differentially expressed upon exposure to different drought stress conditions. Expression analysis of PtHsp70 genes was also examined under drought stress in drought-sensitive and drought-resistant Populus clones with quantitative real-time PCR (qRT-PCR). PtHsp70-16 and PtHsp70-26 genes might provide adaptation to drought stress for both clones. Because of high expression responses to drought in only resistant Populus clone, PtHsp70-25 and PtHsp70-33 genes might be used for determination of drought-tolerant clones for molecular breeding studies. This research provides a fundamental clue for contribution of PtHsp70s to drought tolerance in poplar.
Keywords: 2. Zero hunger; 15. Life on land; 6. Clean water; 3. Good health